2018
DOI: 10.1038/s41531-018-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of subthreshold doses of environmental toxins induces ascending Parkinsonism in the rat

Abstract: Increasing evidence suggests that environmental neurotoxicants or misfolded α-synuclein generated by such neurotoxicants are transported from the gastrointestinal tract to the central nervous system via the vagus nerve, triggering degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and causing Parkinson’s disease (PD). We tested the hypothesis that gastric co-administration of subthreshold doses of lectins and paraquat can recreate the pathology and behavioral manifestations of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 62 publications
(82 reference statements)
0
46
0
1
Order By: Relevance
“…They also made a vagotomy, preventing the progression of PD effects and constraining the appearance of pathological α-syn only to enteric neurons. These reports demonstrated that coadministration of these molecules induces a progressive, l-dopa-responsive PD which is preceded by gastric dysmotility (Anselmi et al, 2018). Finally, it is important to notice the role of the microbiota in the CNS, where the host is constantly controlling the maturation and function of the microglial cells (Cosin-Tomas et al, 2018), a reason to consider their effects and imbalances in the subject, which, in the future, could be key in the control, prevention, or even treatment of PD.…”
Section: The Neuroimmune Context Of Pdmentioning
confidence: 98%
“…They also made a vagotomy, preventing the progression of PD effects and constraining the appearance of pathological α-syn only to enteric neurons. These reports demonstrated that coadministration of these molecules induces a progressive, l-dopa-responsive PD which is preceded by gastric dysmotility (Anselmi et al, 2018). Finally, it is important to notice the role of the microbiota in the CNS, where the host is constantly controlling the maturation and function of the microglial cells (Cosin-Tomas et al, 2018), a reason to consider their effects and imbalances in the subject, which, in the future, could be key in the control, prevention, or even treatment of PD.…”
Section: The Neuroimmune Context Of Pdmentioning
confidence: 98%
“…In humans, truncal but not selective vagotomy has been suggested to have a protective effect towards Parkinson's disease (Liu et al, 2017;Breen et al, 2019). Furthermore, accumulation of α-synuclein, a hallmark of Parkinson's disease, has been detected in ENs (Anselmi et al, 2018) and vagal nerves have been proposed as the key mediator for α-synuclein transport between the ENs and the brain in mice (Santos et al, 2019). α-synuclein was detected in the DMV and substantia nigra (Kim et al, 2019;Van Den Berge et al, 2019) after injection of pathologic α-synuclein into the muscular layer of the pylorus and duodenum, suggesting gut to brain transport of α-synuclein.…”
Section: Tension Receptorsmentioning
confidence: 99%
“…There is a long tradition of investigation into the etiology and pathogenesis of Parkinson's Disease (PD) that seeks to link molecular (pesticides, oxidative stress, protein dysfunction etc.) (Hwang, 2013; Ortiz et al, 2016; Chiti and Dobson, 2017; Anselmi et al, 2018; Stykel et al, 2018) and subcellular (mitochondrial dysfunction etc.) (Henchcliffe and Beal, 2008; Reeve et al, 2018; Tsai et al, 2018) factors with the disease development.…”
Section: Introductionmentioning
confidence: 99%